PENGARUH EFIKASI DIRI TERHADAP KINERJA PNS GURU SMAN WILAYAH II JAKARTA PUSAT - Rohman Hidayatul Attoriq (Mozaic : Islam Nusantara, 2020)
The objective of this research is to obtain information about the effect of self efficacy on performance. It was quantitative research with survey method in SMA N region II Central Jakarta.The research was conducted to all civil servant teachers by using a survey method with path analysis applied in testing hypothesis. The number 117 civil servant teachers as sample was selected by using Slovin formula.The research conlude: There is a direct positive effect of self efficacy on performance.